When EFL learner identity intersects with their investment: Stories from Indonesia - Ubaidillah, M. Faruq; Elfiyanto, Sonny; Rifiyani, Andri Jamaul; Islam, Syaiful (Journal on English as a Foreign Language, 2024)
Current research has looked at learner identity as a single construct and is studied as a separate entity from English as a foreign language (EFL) learners